Migration and Emigration of Species - Madrigal, Álvaro (2004)
Migration and emigration are two forms of disper-sion that are different, basically because of the sea-sonal character of the first, the second is a non re-turn trip; both looking for suitable territories for the survival species. Both are very important for the evo-lution process, specially concerning the speciation and the ecosystem stability. The two phenomena are being affected because of the environmental pro-blems generated by human beings: nowadays, the climatic change is the aspect that threats with the ending of many migratory processes and at the same time to catalyse new emigration processes. In the long  run,  this  would  happen  to  restructure  the ecosystems and their dynamics, facing us to a spe-cies massive extinction.